Applying Discovery Learning Model with Google Classroom to Enhance Mathematics Creative Thinking - Susilowaty, Nora; Simatupang, Yetri (8ISC Abstract Proceedings, 2022)
To improve mathematical creative thinking ability students, a teacher must be creative in creating learning in the classroom. Learning models and facilities are needed to support them. This research used a comparative design to find out whether the enhancement in mathematical creative thinking abilities of students who get a discovery learning model with google classroom is better than students who get only a discovery learning model. This research was conducted on grade VIII students of SMP N 1 Parongpong, West Bandung. The instruments used in this research were test and non-test instruments. The test instrument was a test of mathematical creative thinking ability presented as pre-test and post-test, while the non-test instrument consisted of student responses about learning models, observation sheets. The data were analyzed using the Shapiro-Wilk test and Mann-Whitney test. The results showed that the enhancement of students’ mathematical creative thinking abilities that had a discovery learning model with Google classroom better than students that used discovery learning models only. Student responses to the discovery learning model with Google Classroom and the discovery learning model only are included in the like category. Keywords : Mathematical Creative Thinking Ability, Discovery Learning, Google Classroom